Establishing a Public Resource for Acceptable Surrogate Endpoints to Support FDA Marketing Applications - Agyeman, Abena S.; Siegel, Jeffrey N.; Leptak, Christopher (Frontiers in Medicine, 2022)
Following a comprehensive and coordinated effort between CBER and CDER, FDA established a table of acceptable surrogate endpoints (SEs) to support drug marketing applications. The publicly accessible SE Table was first published in 2018 as a response to the 21st Century Cures Act legislation and is updated every 6 months to reflect current FDA thinking. The criteria for the table headings and content were chosen to foster succinctness and consistency, while reflecting the degree of scientific understanding for each listed SE. Prior to the publication of the SE table there was the misconception that FDA only approved drugs based on a limited number of SEs. Contrary to this viewpoint, the SE table demonstrates that FDA frequently uses SEs as they are used in over 100 disease/use and patient population combinations. This article describes the considerations and approach taken when establishing the SE table as well as a discussion of the benefits and limitations of the SE table when used by various stakeholders.